PERANAN BADAN KEPEGAWAIAN DAERAH DALAM PENEMPATAN APARATUR SIPIL NEGARA PADA JABATAN STRUKTURAL DI KABUPATEN PELALAWAN - Anisa Rezki Utari; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Staffing should be in accordance with the principle of "the right man, on the right place". Staffing directed to staffing in the right position according to their qualifications. But in reality there are many governments who ignore the rules. This phenomenon is used as background research. Regional Employment Board Pelalawan district as one of the government agencies in the area of staffing. The purpose of this study was to determine the role of the Regional Employment Agency Placement Apparatus In the State Civil Structural Position in Pelalawan. This research method is qualitative descriptive.Skunder primary data types. Techniques of data collection was done by interview to the informant who directly related to the title of the study, observation by observation of the object, and documentation of data as literature and references. Based on the results of research on the role of the Regional Employment Board in the State Civil Apparatus Placement on structural positions in Pelalawan can be concluded that the staffing is done by employees of the procurement process. Starting from recruitment, selection, and placement.Keywords: Local Employee Board